Teachers' Professional Development in Oman: Challenges, Efforts and Solutions - Mahfouda Juma Hamed Al Jabri; Heikki Silvennoinen; David Griffiths (Tresorix Ltd, 2022)
Teachers’ in-service training as such is not a new thing in Oman, but due to the national effort put in re-organising and systematising in-service training programmes in the past few years, a whole new phase has emerged in teacher professional development (TPD). The article describes how TPD is responding to the challenges of improving the quality of teaching and learning in Oman. The article also describes the tools used to examine the impact of the provided in-service training. Change in skills of teachers is necessary but not sufficient to make practices and pedagogies change. Results from interviews reveal that teachers encounter a variety of obstacles in schools when trying to make use of what they have learned in TPD programmes. Applying new skills and pedagogies often implies a radical change in established practices and ways of thinking in school culture with unquestionable elements due to long traditions.